Genotype at a promoter polymorphism of the interleukin-6 gene is associated with baseline levels of plasma C-reactive protein. - Vickers, M; Green, F; Terry, C; Mayosi, B; Julier, C; Lathrop, M; Ratcliffe, P; Watkins, H; Keavney, B (2002)
OBJECTIVE: Baseline concentrations of plasma C-reactive protein (CRP) are associated with coronary heart disease. Interleukin-6 (IL-6) regulates CRP gene expression; a promoter polymorphism (-174G/C) of the IL-6 gene has been shown to influence IL-6 transcription but the relationship between genotype at this polymorphism and circulating levels of inflammatory markers remains unclear. We hypothesised that plasma CRP would be a heritable phenotype that would be influenced by genotype at this polymorphism. METHODS: We measured baseline plasma CRP and determined genotypes at the -174G/C polymorphism of the IL-6 gene in 588 members of 98 nuclear families. The heritability of plasma CRP and the association of plasma CRP with genotype were determined using variance components methods. RESULTS: Baseline CRP levels were highly heritable (h(2)=0.39, P<0.0000001). Presence of the -174C allele was associated with higher baseline CRP levels, both in the whole population (P=0.01), and in the founders only (n=128, P=0.001). Family-based analyses confirmed the association (P=0.02) suggesting that it arises from chromosomal proximity or identity of the typed polymorphism with a genetic variant influencing baseline CRP levels. CONCLUSIONS: Baseline plasma CRP is a significantly heritable cardiovascular risk factor. Levels are associated with genotype at the -174G/C polymorphism of the IL-6 gene.